Optical patterns and aesthetic values in the halls of events: رواء مصطفى خلف (Al-Academy, 2016)
current research Cares about study patterns of optical and aesthetic values in the halls of occasions (weddings) because of their importance in providing an atmosphere of joy. The problem was through the study of light and its impact on the receiver and found a researcher that interior spaces allocated to the halls inappropriate in terms of functional and aesthetic so necessitated the need to study this phenomenon in order to be addressed through the study of light and its impact on the users of those spaces where research aims to current detection properties patterns optical in the internal spaces of the halls and identify some of the aesthetic values of the lighting for the interior spaces.The search consists of four chapters, the first chapter the research problem and the importance of research and its objectives and its borders, then the definition of terms used in it so that the reader understands.Represents the second quarter previous studies and the theoretical framework which consisted of three sections, all in the service of the search to achieve its objectives.The third chapter in the research methodology and the actions taken and revealed the reality of the situation and the actions taken to resolve these problems in the interior spaces of those halls then the fourth and final chapter, which included the results of the analysis of samples representing the research community and the conclusions and recommendations